2022
DOI: 10.1039/d2ma00629d
|View full text |Cite
|
Sign up to set email alerts
|

A detailed investigation of the core@shell structure of exchanged coupled magnetic nanoparticles after performing solvent annealing

Abstract: Thanks to important advances in synthesis techniques, a wide collection of bimagnetic core-shell nanoparticles with tunable properties was reported in the literature. Such nanoparticles may combine two phases with different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The pronounced reduction in both H E (10 K) and T onset even for CSSa (for which we estimated above a modest decrease in CoO content from 63% to 51%, see Table 1) suggested that the conversion of CoO into CoFe 2 O 4 was accompanied by the loss of UCS in the remaining CoO, a likely effect of the recently reported effective annealing provided by the third decomposition step. 24 The same effects can be expected from a progressive The decreasing number of CoO UCS (both pinned and rotatable) was conrmed by the difference between the H C values [H C (FC) − H C (ZFC)], which was highest for CS (3.4 kOe) and decreased markedly for the CSS particles (#1 kOe). In short, the concurrent structural ordering of the CoO phase and its hybridization with Co-ferrite from CS to CSSc were consistent with the large reduction in H E across the CS-CSS series (roughly an order of magnitude) while essentially preserving the high coercivity (with a mere 20% decrease in the 10 K loops).…”
Section: Magnetic Propertiesmentioning
confidence: 63%
See 4 more Smart Citations
“…The pronounced reduction in both H E (10 K) and T onset even for CSSa (for which we estimated above a modest decrease in CoO content from 63% to 51%, see Table 1) suggested that the conversion of CoO into CoFe 2 O 4 was accompanied by the loss of UCS in the remaining CoO, a likely effect of the recently reported effective annealing provided by the third decomposition step. 24 The same effects can be expected from a progressive The decreasing number of CoO UCS (both pinned and rotatable) was conrmed by the difference between the H C values [H C (FC) − H C (ZFC)], which was highest for CS (3.4 kOe) and decreased markedly for the CSS particles (#1 kOe). In short, the concurrent structural ordering of the CoO phase and its hybridization with Co-ferrite from CS to CSSc were consistent with the large reduction in H E across the CS-CSS series (roughly an order of magnitude) while essentially preserving the high coercivity (with a mere 20% decrease in the 10 K loops).…”
Section: Magnetic Propertiesmentioning
confidence: 63%
“…Here, the intensity of the S4 peak yielded 23% of the uncompensated Co spins in CS, which mainly consisted of a CoFe 2 O 4 layer localized at the Fe 3− δ O 4 /CoO interface. 24 In CSS nanoparticles, the S4 peak indicated there were much higher amounts of uncompensated Co spins (42%, 54%, and 68% in CSSa, CSSb, and CSSc, respectively). This result unambiguously confirmed the increasing fraction of CoFe 2 O 4 in the nanoparticles at the expense of CoO, completing a consistent structural picture of the particles, as graphically summarized in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations